Anticaries effect of dentifrices with calcium citrate and sodium trimetaphosphate - Delbem, Alberto Carlos Botazzo [UNESP]; Bergamaschi, Mauricio; Rodrigues, Eliana; Sassaki, Kikue Takebayashi [UNESP]; de Mello Vieira, Ana Elisa [UNESP]; Coimbra Missel, Emilene Macario [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2012)
Because of the growing concerns regarding fluoride ingestion by young children and dental fluorosis, it is necessary to develop new dentifrices. Objective: The aim of this study was to evaluate the effect of dentifrices with calcium citrate (Cacit) and sodium trimetaphosphate (TMP) on enamel demineralization. Material and Methods: Enamel blocks (n=70), previously selected through surface hardness analysis, were submitted to daily treatment with dentifrices diluted in artificial saliva and to a pH-cycling model. The fluoride concentration in dentifrices was 0, 250, 450, 550, 1,000 and 1,100 mu g F/g. Crest (TM) was used as a positive control (1,100 mu g F/g). Cacit (0.25%) and TMP (0.25%) were added to dentifrices with 450 and 1,000 mu g F/g. Surface hardness was measured again and integrated loss of subsurface hardness and fluoride concentration in enamel were calculated. Parametric and correlation tests were used to determine difference (p<0.05) and dose-response relationship between treatments. Results: The addition of Cacit and TMP did not provide a higher fluoride concentration in enamel, however it reduced (p<0.05) mineral loss when compared to other dentifrices; the dentifrice with Cacit and TMP and a low fluoride concentration presented similar results when compared to a dentifrice with 1,100 mu g F/g (p>0.05). Conclusions: Dentifrices with 450 and 1,000 mu g F/g, Cacit and TMP were as effective as a gold standard one.
Keywords: Dentifrices; Dental enamel; Fluorides; Calcium citrate; Tooth demineralization